Optimalisasi Kinerja Guru di SD Negeri 61 Kota Banda Aceh Melalui Implementasi Supervisi Ilmiah Berbasis Teknik Percakapan Individu - Royani, Ida; Musdiani, Musdiani; Sariakin, Sariakin (Jayapangus Press, 2024)
This research aims to investigate efforts to improve the performance of teachers at SD Negeri 61 Kota Banda Aceh through the implementation of scientific supervision using individual conversation techniques. Scientific supervision is a systematic approach that enhances teachers' competence and motivation through methods such as observation, data analysis, and personal guidance. The study employs a qualitative approach with a school action research design. Data was collected through in-depth interviews with teachers, classroom observations, and document analysis. The findings indicate that the application of scientific supervision with individual conversation techniques effectively enhances teaching quality and teacher performance. Scientific supervision allows teachers space for self-reflection, constructive feedback, and collaborative planning for improvement with supervisors. Additionally, individual conversation techniques enable supervisors to better understand the personal needs and challenges faced by each teacher. This creates a supportive work environment conducive to teachers' professional growth and improves learning quality at SD Negeri 61 Kota Banda Aceh. These findings can guide the development of educational policies and supervision practices in schools to achieve better learning outcomes.